International Conference on Continuous Media with Microstructure - CONFERENCE, INTERNATIONAL (Engineering Transactions, 2015)
The 2nd conference CMwM is organized in memory of Professor Krzysztof Wilmański who regrettably passed away on 26 August 2012. The 1st conference CMwM took place in Zielona Gόra in 2010 to celebrate the 70th birthday of Professor Krzysztof Wilmański (b. 1 March 1940). Paying tribute to this outstanding scientist we would like to continue the main ideas of the first conference: enriching and extending classical continuum models by various aspects.